Effects of Xylazine-Ketamine Combination on Physiological Parameters in Ovariectomized Senegalensis Domestic Shorthair Cats - Lapo, Rock Allister; Onidje, Edmond; Adamou, Sahidi; Tsangue, Larissa Dongmomo; Serigne, Abdoulaye Cisse; Fall, Gaby (Media Kedokteran Hewan, 2026)
The use of anesthesia in veterinary practice requires careful management to ensure animal welfare during surgical procedures. This study evaluated the effects of the xylazine–ketamine combination on the physiological parameters of Senegalensis Domestic Shorthair cats undergoing ovariectomy at a veterinary clinic in Dakar, Senegal. Twenty-two healthy adult cats were anesthetized with intravenous xylazine (1.1 mg/kg) and ketamine (10 mg/kg). Physiological parameters, including heart rate, respiratory rate, and rectal temperature, were measured at baseline, 15, and 30 min after induction. A significant decrease in rectal temperature occurred at 30 min post-induction (p<0.05), while respiratory rate dropped significantly at 15 min post-induction and partially recovered by 30 min post-induction (p < 0.01). Heart rate remained stable throughout (p = 0.429). Additionally, 45.45% of the cats exhibited urinary incontinence, and 27.27% showed hypersalivation. These findings indicate that xylazine–ketamine anesthesia induces hypothermia and respiratory depression but has minimal impact on heart rate. The study highlights the importance of monitoring these parameters during anesthesia and suggests the need for cautious management, especially with regard to respiratory and temperature control. The results also contribute valuable insights into the efficacy of the xylazine–ketamine combination for small animal surgery in Senegalese veterinary settings.